Data management: an organizational perspective - Watson, Richard T. (New York : Wiley, 1996)
" Complete coverage of database management with the correct balance of business and technical material for the MIS professional. This book covers the technical aspects of database design and implementation, with an equal emphasis on the "why" and "how" of the management of databases, and the managerial uses and philosophy behind databases"--Publisher description.
Sect. 1. The Managerial Perspective -- Sect. 2. Data Modeling and SQL -- Sect. 3. Database Architectures and Implementations -- Sect. 4. Organizational Memory Technologists -- Sect. 5. Managing Organizational Memory. Organizational Memory -- Information -- The Single Entity -- The One-to-Many Relationship -- The Many-to-Many Relationship -- One-to-One and Recursive Relationships -- Data Modeling -- Basic Structures and the Relational Model -- SQL -- The SQL Playbook -- Data Structure and Storage -- Data Storage and Data Processing Architectures -- The Relational Model -- Hierarchical and Network Models -- Object-Oriented Database Management Systems -- Groupware, Hypertext, and Imaging -- Internet and Information Services -- Data Integrity -- Data Administration.
Includes bibliographical references and index.
Keywords: DATABASE MANAGEMENT